Pengenalan Manajemen Pemasaran Pada Siswa Kelas X IPA³ SMAN 04 Kota Bengkulu - Yollandah, Yollandah (Jurnal Kewirausahaan & Inovasi, 2023)
Marketing Management is a branch of knowledge that can be useful for all fields. In the business world, marketing is known as one of the important things in all businesses. Therefore, an introduction to marketing management should be introduced as early as possible to high school students, so that high school students can understand the importance of marketing management from an early age. This community service program aims to introduce marketing management to students of class X IPA ³ at SMA Negeri 04 Bengkulu city. The method used in this activity is the counseling method. The implementation of this activity was carried out for one day on August 15 2023. This community service activity started with counseling as an effort to introduce students to marketing management. By introducing marketing management, it is hoped that it will make it easier for students when they become entrepreneurs when they graduate from high school.